Estimating the Impact of the COVID-19 Pandemic on Maternal and Perinatal Health Care Services in Italy: Results of a Self-Administered Survey - Loredana Cena; Matteo Rota; Stefano Calza; Barbara Massardi; Alice Trainini; Alberto Stefana (Frontiers Media S.A., 2021)
The coronavirus disease 2019 (COVID-19) pandemic is strongly changing the way most people live their lives, and disrupting specialist healthcare systems. Such public health disruptions have resulted in significant collateral damage with particular implications for vulnerable populations, including the perinatal population. This Study aims to estimate the impact of the COVID-19 pandemic on Italian maternal and perinatal health care services. A questionnaire was designed to evaluate the COVID-19 impact on Italian maternal and perinatal healthcare facilities and their activities and provision of services from March to May 2020. The survey was completed by hospital-based and community-based Italian maternal and perinatal healthcare facilities. Most of these were located in Lombardy or Veneto (the most affected Italian regions). 70% of all facilities reported that the first wave of the COVID-19 pandemic negatively influenced the functioning of one or more aspects of the perinatal service; only 28.4% of facilities all over the country continued to provide outpatient routine visits and examinations as usual; 23.4% of facilities became understaffed during the index period due to various reasons such as ward transfer and sick leave. This is the first Italian study, and among very few international studies that describe the effects of the COVID-19 pandemic on antenatal and postnatal healthcare facilities and their provision of activities and services. Our findings confirm that healthcare systems even in high-income countries were not entirely prepared to handle such a global health emergency; indeed, specialized maternal and perinatal healthcare services have been disrupted by this global health emergency.